2018
DOI: 10.3390/ijerph15061262
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationship between Water Diversion and Water Quality of Xuanwu Lake, China

Abstract: Water diversion is often used to improve water quality to reach the standard of China in the short term. However, this large amount of water diversion can not only improve the water quality, but also lead to a decline in the water quality (total phosphorus, total nitrogen) of Xuanwu Lake. Through theoretical analysis, the relationship between water quality and water diversion is established. We also found that the multiplication of the pollutant degradation coefficient (K) and the water residence time (T) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Therefore, in order to reduce the adverse environmental effects, the optimal integration of the processes should be carried out considering the local pollution concentration and the self-purification coefficient of the river water. Song et al [16] reported that large amounts of water diversion can decrease the water quality by carrying organisms from one catchment to another. Therefore, it is necessary to estimate the optimal diversion of water.…”
Section: Water Diversion and Water Transfermentioning
confidence: 99%
“…Therefore, in order to reduce the adverse environmental effects, the optimal integration of the processes should be carried out considering the local pollution concentration and the self-purification coefficient of the river water. Song et al [16] reported that large amounts of water diversion can decrease the water quality by carrying organisms from one catchment to another. Therefore, it is necessary to estimate the optimal diversion of water.…”
Section: Water Diversion and Water Transfermentioning
confidence: 99%
“…The average annual rain is around 1000 mm. The average annual wind velocity is 8 m/s, and the prevailing wind direction is southeast and northwest [ 4 ]. Since 2000, Xuanwu Lake has implemented water diversion engineering, and the water supply reached 50,000 m 3 /d.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Pollution of the water environment has led to the destruction of the ecological status of water, causing water bodies to lose their functions, which in turn has restricted human development. After the water environment is damaged, the ecological function of water bodies is restored by reducing pollutants discharge and water diversion [ 3 , 4 ]. By constructing the urban sewage pipe network, sewage enters the plant for treatment, thereby reducing direct discharge into river [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). The seasonal variations in phytoplankton population may occur due to the changes in the environmental factors through the study period (31). Higher total cell counts may be attributed to the high nutrient values received as domestic disposal that discharge in these stations (32).…”
Section: P-ibi Calculationmentioning
confidence: 99%